Sociable Knowledge : Natural History and the Nation in Early Modern Britain - Yale, Elizabeth (Philadelphia, Pa. : University of Pennsylvania Press, 2015)
Sociable Knowledge reconstructs the collaborations of seventeenth-century naturalists who, dispersed across city and country, worked through writing, conversation, and print to convert fragmented knowledge of the hyper-local and curious into an understanding and representation of Britain as a unified historical and geographical space.
Frontmatter -- Contents -- Note on Sources -- Abbreviations -- t Chapter 2. Putting Texts, Things, and People in Motion: Learned Correspondence in Action -- t Conclusion. Paper Britannias -- Notes -- Bibliography -- Index -- Acknowledgments
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed Sep. 08, 2016)
Keywords: Natural history literature -- Great Britain. -- History -- 17th century; Natural history -- Great Britain -- Historiography. -- 17th century; Topographical surveying -- Political aspects -- Great Britain. -- 17th century; Topographical surveying -- Great Britain -- History -- 17th century